Research on Resource Allocation of Satellite Internet Service Function Based on SDN/NFV - Meilin XU; Min JIA; Qing GUO (天地一体化信息网络)
Software-defined networks and network function virtualization can effectively solve the problems of difficult management and control of large-scale networks and diffi culties in resource scheduling.Applying the software-defi ned network architecture model and network function virtualization technologies to the large-scale satellite internet can eff ectively solve some problems.This paper proposed a new SDN/NFV-based new satellite internet architecture, different satellite domains could be responsibled for different functions, inter-satellite and inter-domain could used SDN and NVF for eff ective collaboration, effi cient used of network resources, research and optimization of its service function resource allocation technology after VNF deployment, a simulated annealing algorithm based on resource awareness was proposed.Simulation results showed that this algorithm could effectively reduced the end-to-end delay and bandwidth consumption of SFC data fl ow during transmission, and could provided users with better services.